Metabolic reprogramming: A novel metabolic model for pulmonary hypertension - Liu, Xuhan; Zhang, Liping; Zhang, Weihua (Frontiers in Cardiovascular Medicine, 2022)
Abstract: Pulmonary arterial hypertension, or PAH, is a condition that is characterized by pulmonary artery pressures above 25 mmhg (at rest). In the treatment of PAH, the pulmonary vascular system is regulated to ensure a diastolic and contraction balance; nevertheless, this treatment does not prevent or reverse pulmonary vascular remodeling and still causes pulmonary hypertension to progress.According to Warburg, the link between metabolism and proliferation in PAH is similar to that of cancer, with a common aerobic glycolytic phenotype.By activating HIF, aerobic glycolysis is enhanced and cell proliferation is triggered.Aside from glutamine metabolism, the Randle cycle is also present in PAH.Enhanced glutamine metabolism replenishes carbon intermediates used by glycolysis and provides energy to over-proliferating and anti-apoptotic pulmonary vascular cells. By activating the Randle cycle, aerobic oxidation is enhanced, ATP is increased, and myocardial injury is reduced. PAH is predisposed by epigenetic dysregulation of DNA methylation, histone acetylation, and microRNA. This article discusses the abnormal metabolism of PAH and how metabolic therapy can be used to combat remodeling.